2018
DOI: 10.1177/1558944717751196
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Complications in Open Versus Endoscopic Carpal Tunnel Release in Private Payer and Medicare Patient Populations

Abstract: In both the Medicare and private insurance patient populations, endoscopic CTR is associated with fewer postoperative complications than open CTR, but is associated with greater expenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
2
36
1
Order By: Relevance
“…Hence, therefore, patients should discuss such pre-existing medical conditions. Also, the patient should tell the doctor about any medications they are using, including herbs, over-the-counter medicines, supplements, and vitamins [27]. In some cases, the physician recommends advises the patient to stop using the medications that would complicate the blood clotting process such as naproxen, aspirin, and ibuprofen [28].…”
Section: Carpal Tunnel Release Surgerymentioning
confidence: 99%
“…Hence, therefore, patients should discuss such pre-existing medical conditions. Also, the patient should tell the doctor about any medications they are using, including herbs, over-the-counter medicines, supplements, and vitamins [27]. In some cases, the physician recommends advises the patient to stop using the medications that would complicate the blood clotting process such as naproxen, aspirin, and ibuprofen [28].…”
Section: Carpal Tunnel Release Surgerymentioning
confidence: 99%
“…8,9 Although small observational studies have been able to investigate the risks of some postoperative infections and nerve injuries, the risk and incidence of reoperation, and rarer complications such as deep infection, have been poorly defined because of limitations in coding systems, and the difficulty in enabling full longitudinal follow-up of patients over time within multiple private healthcare systems, especially those that do not link to official mortality records. [10][11][12][13] Increasingly, evidence from routinely collected data is used to evaluate health-care interventions in the general population. 14 Outcome data from real world practice enables improved counselling of patients both before referral by primary care physicians, and before surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to avoid these complications, Chow [12] and Okutsu et al [13] first reported the use of ECTR for the treatment of CTS in the English literature in 1989. This method allows for smaller skin incisions and better esthetic results than OCTR [1,14,15]. Nevertheless, ECTR is technically difficult, time consuming, and associated with incomplete transverse carpal ligament release and neurovascular injury [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%